The influence of temperature stratification in the lower atmospheric boundary layer on the operating point of a natural draft dry-cooling tower - Hoffmann, Jacob Elisa (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Phil)—Stellenbosch University, 1997.